“Pous van die Kaap”: Koot Vorster en ultra-verkrampte politiek in die 1960’s - Fourie, Ruhan (Stellenbosch Theological Journal, 2024)
“Pope of the Cape”: Koot Vorster and ultra-right politics in the 1960s The Dutch Reformed Church (DRC), with an entrenched relationship with Afrikaner nationalism and apartheid, had to face socio-political changes in Afrikaner society in the 1960s. International pressure on the state, economic prosperity of Afrikaners, cultural exposure to the West, and internal criticism from cultural and academic spaces began to crack the bastion of Afrikanerdom during this decade. While the state had so-called dangers from outside under control at the time, it was the DRC’s focus to strengthen the people from within against unseen dangers such as liberalism and communism. In this context, Dr Koot Vorster emerged from the Cape NG Church as a leading national figure of Afrikaner anticommunism when he became head of the newly established National Council for the Fight against Communism in 1964. This article shows how Vorster was in fact a foreman for an ultra-right political pressure group from the Transvaal. Vorster is therefore considered here as a churchman and “organisation man”, as termed by N.P. van Wyk Louw, within verkrampte ranks. As the political winds blew against the verkramptes under the leadership of Koot’s brother, Prime Minister John Vorster, Koot also stood more and more on the periphery of popular politics as he tested the boundaries at the right of Afrikaner politics. As an organization man he would then stand on the periphery, but as a church man he did not lose his prestige.